Thoroughfares and the deadends of an educational action: a pedagogical adventure - Costa, Antonio Carlos Gomes da (UNICEF Regional Office for Latin America and the Caribbean Santefe de BogotaCO, 1991)
Recounts experiences with the adolescents at the Barbao de Camargos School in Brazil, where girls recognized to have either slight or serious criminal behaviour mixed with adolescent offenders or others that were simply a bit retarded or affected.